2013
DOI: 10.2967/jnumed.113.124172
|View full text |Cite
|
Sign up to set email alerts
|

Early Determination of Prognosis by Interim 3′-Deoxy-3′-18F-Fluorothymidine PET in Patients with Non-Hodgkin Lymphoma

Abstract: PET is a potentially useful modality for response analysis and prognosis prediction in patients with high-grade non-Hodgkin lymphoma (NHL). The thymidine analog 39-deoxy-39-18 F-fluorothymidine ( 18 F-FLT) was recently introduced as a new tracer. 18 F-FLT uptake correlates with tumor cell proliferation and is suggested to reflect early response to treatment. We performed a prospective study to evaluate the prognostic value of early interim 18 F-FLT PET in patients with NHL. Methods: Patients with untreated NHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
3
24
0
1
Order By: Relevance
“…The latter highlights the high risk of iPET misinterpretation, precluding any iPET-driven strategy. In a key study challenging the validity of a positive iPET scan, Moskowitz et al 11 showed that systematic biopsy of iPET4-positive residual mass (ie, with an FDG uptake greater than the local background) after 4 cycles of dose dense rituximab plus cyclophosphamide, oncovin, prednisolone, and hydroxyadriamycine (R-CHOP) only detected active lymphoma, and a commensurate poor prognosis, in 23% of patients, 7 whereas iPETpositive patients with negative biopsy and iPET-negative patients had similar outcomes. With iPET having a false PPV in 87% of cases, they concluded that its clinical predictive value was poor and that it could not be used to drive treatment decisions.…”
Section: Which Methods Is Best For Interpreting Ipet?mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter highlights the high risk of iPET misinterpretation, precluding any iPET-driven strategy. In a key study challenging the validity of a positive iPET scan, Moskowitz et al 11 showed that systematic biopsy of iPET4-positive residual mass (ie, with an FDG uptake greater than the local background) after 4 cycles of dose dense rituximab plus cyclophosphamide, oncovin, prednisolone, and hydroxyadriamycine (R-CHOP) only detected active lymphoma, and a commensurate poor prognosis, in 23% of patients, 7 whereas iPETpositive patients with negative biopsy and iPET-negative patients had similar outcomes. With iPET having a false PPV in 87% of cases, they concluded that its clinical predictive value was poor and that it could not be used to drive treatment decisions.…”
Section: Which Methods Is Best For Interpreting Ipet?mentioning
confidence: 99%
“…Limited data are published about iPET1. [5][6][7] iPET4 often replaces the previously commonly used midtherapy conventional contrast-enhanced CT scan, to ensure that patients have reached at least partial response before proceeding further with treatment. Clinical interest of iPET beyond the fourth cycle is limited, as it usually comes too late to modify the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 18 F-FLT uptake is well correlated with Ki-67 staining in studies of breast, brain and lung cancers [160][161][162][163]. 18 F-FLT has since been used to assess treatment response in breast cancer [164] and lymphoma [165,166], among others. Clinical reports also show that 18 F-FLT is a more reliable and sensitive tracer for evaluating treatment response than 18 F-FDG [167][168][169].…”
Section: Imaging Of Tumor Cell Proliferation During Treatmentmentioning
confidence: 99%
“…Baseline FLT uptake has been shown to be a negative predictor of response to rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) in DLBCL and was significantly correlated with the International Prognostic Index (18). Moreover, preliminary studies have shown that FLT PET allows noninvasive assessment of tumor grading and early response assessment (19)(20)(21)(22)(23)(24).…”
Section: Nuclear Medicine: Early Therapeutic Monitoring Of Dlbcl: Fltmentioning
confidence: 99%